Instabilities and Chaos in Semiconductor Laser With Optical Injection and Feedback - A. Al – Saidi, I.; A. Al – Saymari, F. (University of Thi-Qar Journal of Science, 2019)
A numerical has been under taken to study the effects of the optical injection and the optical feedback on the nonlinear dynamical behavior of the semiconductor laser using a simple model, based on the coupled electric field and population inversion rate equations. A number of distinct states are obtained. These include periodic limit – cycle operation , quasiperiodicity, and chaotic behaviors dependent on the type of the laser control parameter and the operating conditions.